1995
DOI: 10.1136/pgmj.71.837.443
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous multiple lymphomatous polyposis and adenocarcinomata in the large bowel

Abstract: Letters to the Editor Synchronous multiple lymphomatous polyposis and adenocarcinomata in the large bowel Sir, The occurrence of multiple primary malignancies is well-recognised: most cases have involved two or more carcinomata, often of the skin, stomach, colon or breast, and most commonly found in the same organ homolaterally or contralaterally. Cases of synchronous carcinoma and a non-epithelial neoplasm are rarer but still well-documented. Synchronous adenocarcinoma and lym

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
0
18
0
1
Order By: Relevance
“…In addition, the current lymphoma extended systemically and occupied the regional lymph node, thus suggesting that lymphoma preceded the adenocarcinoma and was predominant. Hopster et al 18 postulated that lymphoma predisposes patients to adenocarcinoma due to the lack of immune surveillance; however, there is no evidence that immunodefi ciency induces activation of oncogenes or inactivation of tumor suppressor genes. The extreme rarity suggests that the synchronous development of colonic adenocarcinoma and lymphoma is probably due to chance rather to any specifi c association.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the current lymphoma extended systemically and occupied the regional lymph node, thus suggesting that lymphoma preceded the adenocarcinoma and was predominant. Hopster et al 18 postulated that lymphoma predisposes patients to adenocarcinoma due to the lack of immune surveillance; however, there is no evidence that immunodefi ciency induces activation of oncogenes or inactivation of tumor suppressor genes. The extreme rarity suggests that the synchronous development of colonic adenocarcinoma and lymphoma is probably due to chance rather to any specifi c association.…”
Section: Discussionmentioning
confidence: 98%
“…6 Eighteen case reports have been previously published since Cattell's report in 1947, as shown in Table 1. 5,6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Adenocarcinomas were located in the cecum in 3, in the ascending colon in 2, in the transverse colon in 1, in the descending colon in 1, in the sigmoid colon in 2, and in the rectum in 10 of 19 lesions. On the contrary, lymphomas were located in the cecum in 7, in the ascending colon in 3, in the transverse colon in 1, in the descending colon in 1, and in the rectum in 7 of 19 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that lymphoma might predispose the colon to adenocarcinoma because of altered immune function, allowing for cancerous cells to grow without surveillance. Cornes and others [12][13][14] observed that, in coexisting tumours, adenocarcinomas occur either synchronously with or after a diagnosis of lymphoma in the intestinal tract, suggesting an association between those two cancer types. Nonetheless, the rarity of such cases prevents any firm establishment of a relationship between lymphomas and adenocarcinomas 11,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Jusqu'~ prdsent, un seul cas similaire a 6t6 rapport6 dans la littdrature [18]. Jusqu'~ prdsent, un seul cas similaire a 6t6 rapport6 dans la littdrature [18].…”
Section: Associationsunclassified
“…Up till now there is only one case report of a similar co-occurrence [18]. Up till now there is only one case report of a similar co-occurrence [18].…”
Section: Associationsmentioning
confidence: 99%